Santé de la population francophone et anglophone âgée de 65 ans et plus de l’Ontario [affiche] - Bouchard, Louise; Batista, Ricardo; Duong, Patrick; Sauvé-Schenk, Katrine; Lizotte, Mathieu (Colloque 103 – L’offre des services de santé dans les langues minoritaires, 92e Congrès de l’Acfas, 2025)

From Policy to Practice: A Qualitative Study on Reforms and Frontline Retention in Healthcare - Dubé, Anik; Collin, Stéphanie; Hakim, Jennifer; Johnson, Claire; Laforest, Marie-Ève; Landry, Michel H.; Lauzier, Martin (INQUIRY: The Journal of Health Care Organization, Provision, and Financing, 2025)
In Canada, healthcare reforms typically aim to improve the quality of care and access while making healthcare systems more efficient. These reforms have led to a 2-level healthcare system consisting of provincial and regional health authorities (RHAs). RHAs are responsible for providing and administering health services within specific territories. One of the 2 language-based RHAs in New Brunswick (NB) operates in French-speaking rural minority communities. This study explored key factors affecting the retention of nurses and physicians within a RHA operating in a language minority context. This descriptive qualitative study explored how macro-level decisions are experienced on the frontlines. Data were collected through semi-structured interviews with 21 physicians and 37 registered nurses, as well as 2 focus groups involving 20 key informants in managerial roles. Thematic analysis was used to identify key themes. Three main factors emerged: organizational accountability and frustration, local autonomy and contextual responsiveness, and a culture of openness and perceived loss of control. These factors are associated with policy changes that affect operational settings and resource distribution within the RHA and influence the retention of nurses and physicians. Stakeholders in health system reforms, including governments and RHAs, must recognize that policy adjustments can have direct implications on everyday care. Participants expressed a growing disconnect from decision-making hierarchies and a perceived loss of control. Both are seen as barriers to delivering quality care. Ensuring adequate support and resources for implementing system-level changes is key to fostering professional engagement and enhancing job satisfaction.

La multimorbidité : prévalence et déterminants chez les francophones et les anglophones de l’Ontario [affiche] - Duong, Patrick; Lizotte, Mathieu; Batista, Ricardo; Sauvé-Schenk, Katrine; Bouchard, Louise (Colloque 103 – L’offre des services de santé dans les langues minoritaires, dans le cadre du 92e Congrès de l’Acfas, 2025)

Services de santé dans la langue officielle du patient : liens avec la proximité, la région et les facteurs sociodémographiques - Fernandes, Daphné (Regards sur la société canadienne, 2025)
À l’aide des données tirées de l’Enquête sur la population de langue officielle en situation minoritaire de 2022 et de la Base de données ouverte sur les établissements de soins de santé, la présente étude examine l’incidence de la proximité des établissements de santé, et d’autres facteurs régionaux et sociodémographiques, sur l’accès à des soins dans la langue de choix de la population de langue officielle en situation minoritaire au Canada. Dans cet article, les soins en concordance linguistique se rapportent aux personnes qui reçoivent des services de santé dans la langue officielle de leur choix (français ou anglais). L’analyse porte sur les adultes de 18 ans et plus vivant dans différentes régions du Canada.

Health services in a patient’s own official language: Associations with proximity, region and sociodemographic factors - Fernandes, Daphné (Insights on Canadian Society, 2025)
Using data from the 2022 Survey on the Official Language Minority Population and the Open Database of Healthcare Facilities, this study examines how distance to health care facilities, alongside regional and sociodemographic factors, relates to access to language-concordant care for the official language minority population in Canada. In this article, language-concordant care refers to individuals receiving health care services in their preferred official language (English or French). The analysis focuses on adults aged 18 and older living across Canada.

Practice # 28: Access to Resources in the Community (ARC): A social prescribing and navigation model (Ontario) - Ibrahim, Nour; Benoît, Josée; Savard, Jacinthe (2025)

Pratique # 28: Accès aux ressources communautaires (ARC) : Un modèle de prescription sociale et de navigation (Ontario) - Ibrahim, Nour; Benoît, Josée; Savard, Jacinthe (Dans: GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire., 2025)
Bien qu'il existe de nombreux services et programmes communautaires destinés à répondre aux besoins sociaux et de santé de la population, beaucoup de patients, patientes et médecins généralistes ignorent leur existence, ou peinent à s'y retrouver dnas la multitudes programmes existant. Le modèle ARC est intégré aux soins primaires afin d'aider les patient·es à accéder aux ressources disponibles pour répondre à leurs besoins sociaux et de santé non satisfaits. Cette approche prévoit un point d'entrée unique pour les besoins en santé (non médicaux) et sociaux, amène des changements dans les pratiques afin d'aider les prestataires de soins primaires à mobiliser leur patientèle dans la prise en charge autonome de ces besoins, et fait appel aux services d’un·e navigateur·trice communautaire non clinique, chargé d’accompagner les patient·es dans l’accès aux ressources communautaires appropriées. Parmi les caractéristiques du modèle, on retrouve un acompagnement linguistique bilingue : Les navigateurs et navigatrices ARC sont formés pour offrir un soutien linguistique en français et en anglais pour répondre aux besoins des patient·es, adoptent une approche d’« offre active » et veillent à ce que les patient·es puissent accéder facilement et confortablement aux services et à l’information dans la langue de leur choix.

Impact de la crise de la COVID-19 sur les familles francophones dans les Prairies canadiennes - Leis, Anne; De Moissac, Danielle; Proulx-Cullen, Elyse; Gnidehou, Sedami; Marchak, Kristan A.; Keough, Catelyn; Chaput, Mélanie; Turgeon, Marianne (Minorités linguistiques et société, 2025)
Résumé Contexte et but. Dans le contexte linguistique minoritaire où l’accès à des services en français est un défi, l’étude voulait documenter dans quelle mesure la crise de la pandémie avait eu un impact sur les familles francophones au Manitoba, Saskatchewan et Alberta. Méthodes. À partir des informations recueillies lors de 6 World Café du Monde, un sondage a été créé et distribué en ligne aux membres d’organismes francophones dans ces provinces. Des analyses descriptives et de régression ont été menées. Résultats. Des 319 familles, la grande majorité a reconnu l’impact négatif et anxiogène de la pandémie. Plusieurs facteurs de risque ont été identifiés : une compréhension moyenne ou faible de l’anglais, la déconnexion avec la communauté francophone locale, la difficulté de vivre en français en famille et de suivre la scolarité de ses enfants à la maison. Conclusion. La pandémie a été un défi pour les familles francophones des Prairies. Des ressources accrues en français et des politiques de soutien sont recommandées. Abstract Background and aim. Within the linguistic minority context where access to services in French is a challenge, the study aimed to document to what extent the pandemic had an impact on Francophone families in Manitoba, Saskatchewan and Alberta. Methods. Based on the qualitative analysis of data collected in 6 World Cafés, an on-line survey was distributed to members of Francophone organizations in these provinces. Descriptive and regression analyses were conducted. Results. Of 319 families, the majority recognized the negative and anxiety provoking aspects of the pandemic. Several risk factors were identified: an average or below average mastery of English, isolation from the local Francophone community, difficulty with living in French with their family and supporting children’s education at home. Conclusion. The pandemic was a challenge for Francophone families in the Prairies. Additional resources in French and supportive policies are recommended.

Operationalising linguistic unease for the evaluation of language policies in healthcare - Marinaro, Nicole (Revista de Llengua i Dret, 2025)
This contribution presents an original methodological tool for the systematic evaluation of the relevance and comprehensiveness of healthcare language policy design. In particular, the focus of the analysis are public policies that address communication barriers experienced by patients who speak autochthonous or allochthonous languages other than the majority language in their interaction with the healthcare system. Such communication barriers are here conceptualised as “linguistic unease”. Within the epistemological framework of public policy analysis, the tool presented in the article hinges on the operationalisation of the concept of linguistic unease and is hence built on the centrality of the consideration of speakers’ needs. After outlining instances of linguistic unease in healthcare, the article presents the tool in detail and illustrates its employment through a brief practical example. , Aquest article presenta una eina metodològica original per a l’avaluació sistemàtica de la rellevància i l’exhaustivitat del disseny de polítiques lingüístiques en l’atenció sanitària. En concret, l’anàlisi se centra en les polítiques públiques que aborden les barreres de comunicació que experimenten els pacients que parlen llengües autòctones o al·lòctones diferents de la llengua majoritària a l’hora d’interactuar amb el sistema de salut. Aquestes barreres comunicatives es conceptualitzen com a “incomoditat lingüística”. Dins del marc epistemològic de l’anàlisi de les polítiques públiques, l’eina presentada a l’article es basa en l’operacionalització del concepte d’incomoditat lingüística i, com a tal, s’articula al voltant de la centralitat de les necessitats dels parlants. Després d’exposar diversos casos d’incomoditat lingüística en l’atenció sanitària, l’article descriu l’eina en detall i n’il·lustra l’ús a través d’un breu exemple pràctic. , Este artículo presenta una herramienta metodológica original para la evaluación sistemática de la relevancia y la exhaustividad del diseño de políticas lingüísticas en la atención sanitaria. En concreto, el análisis se centra en las políticas públicas que abordan las barreras de comunicación que experimentan los pacientes que hablan lenguas autóctonas o alóctonas diferentes de la lengua mayoritaria en sus interacciones con el sistema de salud. Estas barreras comunicativas se conceptualizan como “incomodidad lingüística”. Dentro del marco epistemológico del análisis de las políticas públicas, la herramienta presentada en el artículo se basa en la operacionalización del concepto de “incomodidad lingüística” y, como tal, se articula en torno a la centralidad de las necesidades de los hablantes. Después de exponer varios casos de incomodidad lingüística en la atención sanitaria, el artículo describe la herramienta en detalle e ilustra su uso a través de un breve ejemplo práctico.

Validation culturelle d’un outil numérique francophone pour l’histoire médicale en soins de santé primaires - McGraw, Monica; Dionne Merlin, Marjolaine; Dion, Cynthia; Renaud, Julie; Légère, Danika; Poirier, Marie-Dominique (Minorités linguistiques et société / Linguistic Minorities and Society, 2025)
La technologie de santé numérique s’intègre dans les soins de santé améliorant l’engagement des patients dans les décisions partagées, favorisant ainsi leur prise en charge et la qualité des soins. FirstHx développe des outils innovants dans cette optique, mais leur mise en oeuvre est complexe pour la population francophone dans un contexte majoritairement anglophone. Cette étude vise à valider culturellement cet outil et à évaluer la satisfaction des utilisateurs. Une méthodologie mixte séquentielle explicative est employée en trois phases : un sondage quantitatif pour tester la clarté des questions, des entretiens semi-dirigés pour explorer la traduction culturelle et la convivialité, et une validation par des experts via la méthode Delphi. L’outil validé optimisera les pratiques cliniques, normalisera la saisie des données d’anamnèse et ouvrira de nouvelles perspectives de recherche. Cette validation offrira à la population francophone un accès équitable à des outils numériques innovants, renforçant leur engagement dans leurs soins. Digital health technology is being integrated into healthcare, improving patient engagement in shared decision-making, thereby promoting their care and the quality of care. FirstHx develops innovative tools with this goal in mind, but their implementation is complex for the Francophone population in a predominantly English-speaking context. This study aims to culturally validate this tool and assess user satisfaction. A sequential explanatory mixed-method approach is used in three phases: a quantitative survey to test question clarity, semi-structured interviews to explore cultural translation and user-friendliness, and validation by experts using the Delphi method. The validated tool will optimize clinical practices, standardize the collection of medical history data, and open new research opportunities. This validation will provide the Francophone population with equitable access to innovative digital tools, strengthening their engagement in their healthcare.

Examining the impact of two patient navigation models within a social prescribing program on self-reported health service utilization and health-related quality of life (Doctoral dissertation, Laurentian University Library & Archives) - Pitre, Joël (2025)
Abstract Background: Social prescribing programs have shown promise for addressing the healthcare system fragmentation and the negative impact of certain social determinants of health. They entail primary care providers referring patients with unmet health or social needs to community resources, a process that is mediated by a lay navigator, who assists patients in identifying barriers and facilitating access to the appropriate resources. Although Ontario 211 and the Access to Resources in the Community (ARC) intervention both utilize lay navigators to assist their patients, the former provides informational services to its patients, whereas the latter offers more comprehensive and reoccurring support to patients. Study Objective: This study compared the impact of both navigation models within a social prescribing program setting on patient self-reported health service utilization and health-related quality of life. Methods: A secondary analysis was conducted using data collected in 2018/19 during the randomized control trial (RCT) comparing ARC and Ontario 211 navigation. Three hundred and twenty-six patients were enrolled in the study, and 237 patients completed the post-intervention questionnaire. Participants were adults who had identified an unmet health or social need and frequented a primary care provider. Health service utilization outcomes included the number of emergency department (ED) visits and hospitalizations, while the health-related quality of life was assessed with the validated Veterans RAND 12 questionnaire. Unadjusted and adjusted regression analyses were conducted to compare outcomes between both navigation models, controlling for socio-demographic characteristics. Results: Although none of the results reached statistical significance, participants assigned to the ARC navigation intervention had an apparent higher odds of ED visits and modestly improved physical quality of life yet had relatively similar odds of hospitalization and improvement in mental quality of life compared to those in the Ontario 211 arm. Conclusion: Despite not demonstrating statistically significant associations, the results provide insight into the emerging field of social prescribing in Canada. In today’s political and economic landscape, with a healthcare system focused on addressing social determinants of health, there remains an ongoing need for innovative evaluations of preventative interventions. While effects may not always be observed immediately, as in these findings, with continued research, social prescribing programs show potential for leading the way to equitable care. Keywords: Social prescribing, emergency department, hospitalization, health-related quality of life, patient navigation

Patient-Physician Language Concordance and Cardiovascular Outcomes Among Patients With Hypertension. - Reaume, Michael; Labossière, Mathieu N.; Batista, Ricardo; Van Haute, Stephanie; Tangri, Navdeep; Rigatto, Claudio; Bohm, Clara; Prud’homme, Denis; Tanuseputro, Peter; Lix, L. M. (JAMA Network Open, 2025)
Importance: Patients who live in minority language communities often receive health care services of lower quality and safety compared with patients who speak the majority language. Yet the outcomes associated with care provided by physicians who speak a patient’s primary language remain unknown. Objective : To examine patient-physician language concordance and the risk of major adverse cardiovascular events (MACEs) among patients with hypertension. Design, Setting, and Participants This retrospective cohort study identified adults with self-reported hypertension in the Canadian Community Health Survey, a national survey that collects data from a representative sample of Canadians, from January 1, 2003, to December 31, 2014. Respondents (excluding those living in Quebec) had their hospitalization and mortality records linked to their survey responses. Data were analyzed from October 2023 to May 2024. Exposures: Respondents’ primary home language was defined using language spoken most often at home. Language spoken with a regular physician was used to measure patient-physician language concordance. Respondents who spoke to their regular physician in their primary home language were classified as having received language-concordant care, while all other respondents were classified as having received language-discordant care. Main Outcomes and Measures MACEs within 5 years of survey completion. Results : Among the 124 583 patients included in this study, 114 239 (91.7%) spoke English, 4790 (3.8%) spoke French, 325 (0.3%) spoke an Indigenous language, and 5229 (4.2%) spoke an allophone (ie, other) language. The mean (SD) age of the cohort was 63.7 (14.8) years; 57.1% of the patients reported their sex as female. Very few respondents who spoke an Indigenous language at home (<4.6%) received language-concordant care. For French-speaking patients, there was no statistically significant difference in the risk of MACE between those who received language-concordant care and those who received language-discordant care (hazard ratio [HR], 1.09; 95% CI, 0.86-1.36). Allophone-speaking patients who received language-concordant care were 36% less likely to experience MACE (HR, 0.64; 95% CI, 0.51–0.80) compared with allophone-speaking patients who received language-discordant care. Conclusions and Relevance: This retrospective cohort study found large disparities in both access to language-concordant care and risk of MACEs. These findings suggest that language-concordant care could potentially improve the health of individuals in minority language communities.

Understanding patient barriers and enablers to accessing community resources: a qualitative study to inform navigation service delivery - Saluja, Kiran; Mahbub, Adiba; Gauthier, Alain P.; Lemonde, Manon; Timony, Patrick; Durand, François; Dahrouge, Simone (BMC Primary Care, 2025)
Abstract Background Individuals face multifaceted barriers to accessing community resources, which can significantly impact their ability to obtain necessary support and services. This study examines barriers and enablers to access community resources among primary care patients and explores the interplay between individual- and system-level factors that influence access to resources. Methods In this qualitative study, we conducted 32 semi-structured interviews with primary care patients who participated in a social prescribing trial that compared two navigation services: ARC (patient-centered longitudinal support) vs. Ontario-211 (free 24-hour helpline service) in two regions, Ottawa and Sudbury, in the province of Ontario, Canada. We conducted thematic data analysis with a deductive/inductive hybrid approach, employing Levesque’s theoretical framework for access to health that examines the various system and individual level factors influencing access to healthcare services. Findings At the system level, various systemic barriers encompassing broader organisational, structural, and policy-related elements influenced patients' access to community resources (outreach, availability, location, costs and accommodations for patient needs and preferences). These factors directly interacted with various patient-level factors (awareness of needs, ability to seek support, to reach resources and to pay for those, their physical and mental health, motivation, and confidence to engage in care) to determine access. Conclusions Our findings highlight individual- and system-level barriers and enablers for accessing community resources among socially complex primary care patients with multiple unmet needs. As governments and organizations in Canada are increasingly investing in community-based services to address adverse social determinants of health (SDH), an upstream approach that reduces both systemic and individual-level barriers to access is warranted. Language significantly influences access to services, particularly for linguistic minorities (see page 5 and 7)

Soutien aux proches-aidants francophones en situation minoritaire dans le contexte nordique : la contribution de la dynamique communautaire partenariale du Nord de l’Ontario au vieillissement à domicile - Siméon, Frantz; Célestin, Guison; Couturier, Yves; Larocque, Sylvie; Timony, Patrick (2025)
Faits saillants Cette recherche confirme et soutient : 1. Le fait que la proche-aidance se conjugue presque exclusivement au féminin. Deux facteurs expliquent ce fait de notre point de vue : (1) les femmes sont plus nombreuses au grand âge, donc sont statistiquement plus représentées dans le rôle que les hommes, (2) la socialisation des femmes au rôle du prendre soin et son intégration par celles-ci comme allant de soi témoigne d’une légitimation à priori de l’idée que le poids de l’aidance relève naturellement de la femme. 2. Que l’aidance en contexte minoritaire francophone est un travail qui va au-delà du temps plein ; la personne proche-aidante, indépendamment du degré de perte d’autonomie de la personne aidée, doit être présente 24 h/24, 7 j/7. Elle exige à la fois de l’intervention directe (prendre soin de son proche, l’accompagner, le soutenir…) et de l’intervention indirecte (assumer la coordination des services, plaider pour les services en français…). 3. Qu’entre le discours politique sur le soutien à domicile et la réalité des proches-aidantes en contexte francophone minoritaire, il y a un écart énorme à combler par des mesures concrètes de soutien et d’accompagnement. Ces mesures nécessitent d’importants investissements, notamment dans le financement des organismes de proximité qui constituent un filet de sécurité de première ligne pour un vieillissement à domicile à la hauteur des attentes des aînés francophones.

French among Health Care Workers in Canada Outside Quebec, 2021 (Infographic) - Statistics Canada (2025)

Language indicators over time: Interactive Dashboard - Statistics Canada (Statistics Canada, 2025)

Table : 15-10-0041-01 Frequency of health care or services obtained in the minority official language, by age group and gender, for adults in the official language minority population - Statistics Canada (Gouvernement du Canada, 2025)
Health services or care in the minority official language by age group and gender, Canada, among adults in the minority official language population who considered it important to obtain health services or care in the minority official language, 2022. Possibility to conduct more specific searches for Quebec, Canada outside Quebec, certain provinces, or certain regions.

Indicateurs linguistiques au fil du temps : tableau de bord interactif - Statistique Canada (Statistique Canada, 2025)

Le français chez les travailleurs et travailleuses de la santé au Canada hors Québec, 2021 (infographie) - Statistique Canada (2025)

Rethinking the way we measure access to language-concordant health services for minority language populations: a secondary analysis of publicly available physician and population data in Ontario, Canada - Timony, Patrick E.; Belanger, Christopher; Bélizaire, Arlynn; Desilets, Antoine; Gauthier, Alain; Karunananthan, Sathya; Muray, Mwali-Nachishali; Peixoto, Cayden; Fitzsimon, Jonathan Peter; Godfrey, Leanda; Bjerre, Lise M. (BMJ Open, 2025)
Abstract Objective Providing care in a patient’s preferred language improves health outcomes and patient satisfaction. In Ontario, access to French-speaking physicians (FSPs) is estimated using FSP-to-Francophone population ratios and compared with total physician-to-total population ratios. This approach fails to consider the fact that FSPs also serve non-Francophone patients and that Francophones must compete with the entire population to access FSPs. As a result, this approach inaccurately suggests that Francophones have better access to language-concordant care than Anglophones/Allophones. We propose a novel approach to address this issue, enabling unbiased comparisons of access to language-concordant care across linguistic groups. Design This secondary analysis of publicly available data containing linguistic variables for the Ontario population (Statistics Canada, 2021 Census) and for family physicians (FPs) (College of Physicians and Surgeons of Ontario, January 2024) calculated competition-adjusted ratios and probabilities of accessing language-concordant care. Setting Ontario, Canada. Participants Census and publicly available data on FPs (ie, those providing comprehensive family medicine care to the community) and the Ontario population were obtained. Results Province-wide, the crude ratio of FSPs per 1000 Francophones was 3.46. After adjusting for competition, the ratio of FSP per 1000 population was 0.12, compared with a general physicians-per-1000 population ratio of 1.05. Anglophones/Allophones attached to a FP have a 100% probability of receiving care in English compared with an 11.4% probability for Francophones to receive care from a FSP. Expressed otherwise, Anglophones/Allophones are 8.8 times more likely to receive language-concordant care (ie, care in English) than Francophones. Conclusions Although crude physician-to-population ratios overestimate Francophones’ access to FSPs, competition-adjusted ratios and probabilities demonstrate that they are much less likely to access language-concordant care than Anglophones/Allophones. This novel approach has equity implications for health human resources planning and can be applied to other linguistic minority groups and healthcare providers.

Pratique # 25 : Accès éQUITÉ : Simplifier l’accès aux services de santé en français (Société Santé en français) - van Kemenade, Solange; Benoît, Josée; Savard, Sébastien; Savard, Jacinthe (Dans: GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire., 2025)
Ayant remarqué que certains gestionnaires démontraient une volonté d’améliorer les services en français au sein de leur organisation sans savoir comment s’y prendre, la Société Santé en français (SSF) et les réseaux de santé en français ont développé la plateforme en ligne accès éQUITÉ, dans le but d’accompagner les organisations dans la mise en place durable des services de santé en français. La Plateforme accès éQUITÉ regroupe des outils validés et fondés sur des données probantes qui aident les organisations à comprendre la marche à suivre pour mettre en place des pratiques exemplaires. Il s’agit d’une ressource conviviale comprenant divers modules de formations qui permettent aux gestionnaires d’évaluer les capacités de leur organisation à fournir des services de santé en français et d’améliorer leur prestation en suivant, à leur rythme, la démarche proposée. De plus, cette démarche est accompagnée d’un soutien personnalisé offert par des experts. Les ressources d’accès éQUITÉ aident les organisations à se préparer lorsqu'elles souhaitent présenter une demande au programme de reconnaissance des langues officielles (PRLO) d’Agrément Canada (fondée sur la norme "Accès aux services de santé et aux services sociaux dans les langues officielles"). De plus, à titre individuelle, toute personne membre certifié du Collège canadien des leaders en santé (CCLS) qui complète les formations disponibles dans accès éQUITÉ peut recevoir des crédits à l’égard des exigences de certification de cet organisme.